AB0629 Neutrophil/Lymphocyte Ratio and Mean Platelet Volume in Behçet's Disease. (9th June 2015) - Balkarli, A.; Kucuk, A.; Babur, H.; Erbasan, F.
Abstract : Background: Behçet's disease does not have specific laboratory findings or a pathological physical examination sign. There are many suggested markers for inflammation in BD. Studies on this issue have shown that IL-6, IL-1β, TNF-α, thrombomodulin, E-selectin, VEGF, total homocysteine, α-1 antitrypsin, α-2 macroglobulin are the considered markers associated with BD. Recently, reports have concluded that the neutrophil/lymphocyte ratio (NLR) and mean platelet volume (MPV) are indicators for systemic inflammation. To the best of our knowledge, there is no research in the literature that evaluates both MPV and N/L ratio for patients with Behçet's disease. Objectives: With this retrospective study, we researched the effects of MPV and NLR on the activity of Behçet's disease and susceptibility to thrombosis. Methods: 186 patients with Behçet's disease, who met the inclusion criteria, were separated into two groups as following: 120 patients with active Behçet's disease (Group I) and 66 patients with inactive Behçet's disease (Group II). 79 healthy subjects as controls were included in the study. Results: MPV was similar between all three groups. CRP was statistically higher in the active BD group when compared to the inactive BD group and the control group. CRP of the inactive BD and the healthy control group were similar. In addition, ESR was found higher than the control group in both active and inactive BD groups, whereas ESR of the active BD group was higher than the inactive BD group. N/L ratio was found statistically higher in the active BD group when compared to inactive BD and healthy control groups, while the N/L ratio of inactive BD and healthy control groups were found similar to each other. While MPV, CRP, and NLR didn't statistically differ between active BD subgroups with and without thrombosis, ESR was statistically and significantly higher in the active BD group with thrombosis when compared to the active BD group without thrombosis. Conclusions: The data obtained from the present study showed that the patients with BD are exposed to chronic inflammation. And the N/L ratio may be a simple, inexpensive, and convenient diagnostic marker of active BD. Disclosure of Interest: None declared